Procurement Performance and Supplier Management Measurement Issues: A Case of Malaysian Private Company - Mohd Nawi, Mohd Nasrun; M., Songappenm; Nadarajan, Santhisegaran; Ibrahim, Siti Halipah; Mustapha, Ramlee (International Journal of Supply Chain Management, 2017)
The rising material and operational cost for manufacturers in medical device industry is of concern to many organizations. As such, it’s imperative measurement of procurement and supplier performance established which will enable competitive advantage and provide a framework to stakeholders for continuous improvement. The main objective of this paper is to develop a procurement and supplier performance measurement system at ABC Sdn Bhd (not real name). By conducting literature reviews in procurement performance measurement and supplier performance measurement. Key components of supply chain together with the resources, procedures and output, a model is been developed.  Additionally, a system has been established with a set of generic measures and six perspectives. The case study conducted at the ABC Sdn Bhd.  Medical applies to model develop to describe the procurement department within the supply chain activities. Results shows supply chain department has already made a good progress in measuring procurement process through the implementation of supplier development program. Data that are manually collected but not properly utilized. Few areas need to measure include cycle time of delivery, order processing time, effectiveness, efficiency and reliability. Though a lot of hard work was involved, the advantages of establishing a measurement system outweigh the costs and efforts involved in its implementation. Results of key performance index measurements provide stakeholders with critical information on efficiency and effectiveness of the procurement department’s work.